PD‐1+ TIM‐3+ T cells in malignant ascites predict prognosis of gastrointestinal cancer. Issue 9 (5th September 2018) - Nakano, Michitaka; Ito, Mamoru; Tanaka, Risa; Yamaguchi, Kyoko; Ariyama, Hiroshi; Mitsugi, Kenji; Yoshihiro, Tomoyasu; Ohmura, Hirofumi; Tsuruta, Nobuhiro; Hanamura, Fumiyasu; Sagara, Kosuke; Okumura, Yuta; et al.
Abstract: The liquid biopsy of ascites fluid could be an excellent source of tumor and microenvironment for the study of prognostic biomarkers because of its accessibility. Tumor‐infiltrating lymphocytes (TILs) can predict prognosis in multiple malignancies, including the response to immune checkpoint inhibitors, a breakthrough cancer therapy. However, TILs' profiles from malignant ascites have not been extensively studied. Using flow cytometric analysis, we quantified the proportion of exhausted T cells and memory/naive/effector T‐cell subsets, among the CD4+ and CD8+ T‐cell populations of paired TILs and peripheral blood T cell samples (n = 22). The correlation between CD4+ and CD8+ subset profiles suggested that the combined analysis of CD4+ and CD8+ cells in malignant ascites was clinically significant. We found that cells positive for the exhaustion markers programmed cell death‐1 (PD‐1), and T‐cell immunoglobulin and mucin domain 3 (TIM‐3), and cells coexpressing PD‐1 and TIM‐3 abundantly exist among malignant ascites TILs. Furthermore, patients with high frequency of PD‐1+ TIM‐3+ cells among the CD4+ and CD8+ T‐cell population showed worse clinical outcome in multivariate analysis (n = 27). We propose that exhausted ascites TILs represent a clinically significant prognostic biomarker in advanced gastrointestinal cancer and represent an important target for immune checkpoint inhibitors. Abstract : PD‐1+ and Tim‐3+ T cells are enriched within malignant ascites. Among them, PD‐1+ Tim‐3+ ascites TILs are the useful predictive biomarkers in gastrointestinal cancer with malignant ascites.